Clinicopathological study of minor salivary gland tumour - Rashid, Md Shazibur; Bhuiyan, Mohammad Ashequr Rahman; Islam, Mohammad Shafiqul; Siddiquee, Belayat Hossain (Bangladesh Journal of Otorhinolaryngology, 2011)
Objectives: To find out the clinicopathological factors of minor salivary gland tumour. Methods: An attempt has been made to explore the relative incidence, clinical presentation, age and sex distribution, histological type, site of involvement of each cases of minor salivary gland tumour. Thirty cases of minor salivary gland tumours were studied. Sampling method was purposive, convenient. Data were collected in a prescribed data sheet from BSMMU, DMCH and BKZMC and SSH, Dhaka, during the period of October 2006 to May 2007. Results: In this series of 30 patients, 20 cases (67%) were found malignant and 10 cases (33%) were benign. Regarding the site of distribution of minor salivary gland tumour, 67% (20) were found in the hard palate, three patients were found in the soft palate, three patients in the check, two in the nasopharynx and two in the alveolar margin. All benign tumours in this series were pleomorphic adenoma. Monomorphic adenoma was not found in any patients. Among malignant tumour adenoid cystic carcinoma was the most common 70% (14). Pleomorphic adenoma was found in 33% (10) of total cases. Muco-epidermoid carcinoma was the 2nd most common malignant tumour 12.5% (4). Carcinoma in pleomorphic adenoma was the least common histological type 6% (2). Conclusion: Early diagnosis and treatment of minor salivary gland tumour is likely to lead to a fair outcome. All patients with swelling in hard palate should be considered as a minor salivary tumour. Sub clinical lymphatic metastasis may occur in malignant cases, so all patients should be referred for radiotherapy following surgery. Distant metastases are also rare in such type of malignancy. Key words: Minor salivary gland; Neoplasm. DOI: 10.3329/bjo.v17i1.7628 Bangladesh J Otorhinolaryngol 2011; 17(1): 48-52